The Effect of Using Teaching Aids For Developing Explosive Power and Their Effect On Performing Some Shooting Skills In Basketball Players U18 - Abedulsattar, Muhanned; Majeed, Omar (Journal of Physical Education, 2019)
The importance of the research lies in using assisting aids for developing players physically especially explosive power and shooting skills in basketball. The problem of the research lies in not paying enough attention to the players’ physical preparation. The researchers used the experimental method. The subjects were (8) basketball players U18 from the national gifted center for basketball/Ministry of Youth and sport. The data was collected and treated using proper statistical operations to come up with the conclusions. The researchers concluded development in explosive power and some offensive skills in basketball. The researchers recommended using teaching aids in training to develop physical performance. Finally they recommended the necessity of paying attention to physical abilities training using training aids.